Characterization of the 2019/20 english football champion's counterattack - Sartori, João Pedro Caetano (2023)
The counterattack is an attack method that aims to exploit the opponent's defensive vulnerability now of offensive transition. It is also believed in the interference of contextual variables as possible conditioners of sports behaviors (Marcelino, Sampaio, Mesquita, 2011). The objective of the study was to characterize the counterattack of a soccer team, verify its effectiveness and its incidence regarding the place of the game, the game time, and the momentary result of the game. The sample consisted of 143 counterattacks from 12 games of the English Premier League 2019/20, corresponding to six “home” games and six “away” games. The study was carried out through an objective and non-participant systematic analysis. The SPSS IBM version 20 statistical program was used to perform the chi-square test, with a significance level set at p < 0,05. The results indicate that the team starts the counterattack in the central areas of the field, especially in the defensive sectors, with "Constant pressure and recovery in the defensive field" from interception, performs the first forward pass, with 0 to 3 players to in front of the first carrier, exchanges up to 2 passes, involving up to 2 players, does not occupy the three aisles of the field and enters the offensive sector through the central aisle, with a tendency to lose the ball without finishing the opponent's goal. Furthermore, the incidence of actions did not change in terms of game location and game time but was different in terms of the match status.